Internal Audit and Financial Performance of Quoted Manufacturing Companies in Lagos State, Nigeria - Adu , Cecilia Adurayemi; Olusesi, Hakeem Olalekan; Adewale , Johnson Akomolafe; Ezeugonwa , Linda Uzoma (Indonesian Journal of Banking and Financial Technology, 2024)
The study examined the effect of internal audit on financial performance of quoted manufacturing companies in Lagos state while the specific objective was to determine the effect of audit scope on the profitability of quoted manufacturing companies.The population of the was five hundred employees from which a sample size of sixty was selected through purposive sampling technique.  It was revealed by the study that there was a positive relationship between internal audit and financial performance of quoted mmanufacturing companies; that audit scope had significant effect on the profit made by manufacturing companies with R2=34%, (P<0.05). It was suggested that the scope of audit should be expanded to cover all critical operational areas to have a comprehensive evaluation of the company’s processes and controls.